Heat Treatment of Milk: A Rapid Review of the Impacts on Postprandial Protein and Lipid Kinetics in Human Adults - Fatih, Mona; Barnett, Matthew P. G.; Gillies, Nicola A.; Milan, Amber M. (Frontiers in Nutrition, 2021)
Background: Most milk consumed by humans undergoes heat treatment to ensure microbiological safety and extend shelf life. Although milk heat treatment impacts on its structure and physiochemical properties, these effect on the absorption of nutrients in humans is not clear. Therefore, a rapid review was performed to identify studies conducted on healthy human adult subjects that have assessed the impacts of heat treatment of milk on protein and fat digestion and metabolism in the postprandial period (up to 24 hours). Methods: Relevant databases (Medline, EMBASE, Cochrane, Scopus) were systematically screened for intervention studies on healthy adult men and women that assessed the impact of consuming heat-treated milk on the postprandial kinetics or appearance in peripheral circulation or urine of ingested proteins and/or lipids. The risk-of-bias assessment tool 2 was used for quality assessment. Results: Of 511 unique database records, 4 studies were included (n=57 participants, 20-68 years). Three studies evaluated pasteurization, two evaluated ultra-high temperature (UHT) treatment, and one evaluated oven-heated milk. Protein and lipid appearances in peripheral blood were reported in two sets of two studies. None of the studies used the same heat treatments and outcome measures, limiting generalization of effects. Protein appearance (ng/mL or area under the curve) (as plasma amino acids - lysine) was reduced when milk was oven-heated for 5 h in one study (n=7 participants), while the other study reported a reduced retention of dietary N with UHT milk (n=25 participants). Overall plasma triacylglycerol responses were unaffected by milk heat treatments reported, but fatty acid composition differed. The studies observed higher plasma myristic and palmitic acid abundance with successive heat treatment at 2 h (n=11 participants; pasteurized) and 4 h (n=14 participants; UHT) after ingestion; other differences were inconsistent. All studies had moderate-high risk of bias, which should be taken into consideration when interpreting findings. Discussion: This review identified few studies reporting the effects of milk heat treatment on postprandial nutrient responses in adults. Although the findings suggest that milk heat treatment likely affects postprandial protein and lipid dynamics, generalization of the findings is limited as treatments, outcomes, and methods differed across studies.